A convergent, umpoled synthesis of 2-(1-amidoalkyl)pyridines - Johnson, Tarn C.; Marsden, Stephen P. (Beilstein Journal of Organic Chemistry, 2016)
A convenient, one-pot, two-component synthesis of 2-(1-amidoalkyl)pyridines is reported, based upon the substitution of suitably-activated pyridine N-oxides by azlactone nucleophiles, followed by decarboxylative azlactone ring-opening. The synthesis obviates the need for precious metal catalysts to achieve a formal enolate arylation reaction, and constitutes a formally ‘umpoled’ approach to this valuable class of bioactive structures.
Keywords: azlactones; pyridines; pyridine N-oxides; substitution

(untitled) - Carey, J. S.; Laffan, D.; Thomson, C.; Williams, M. T. (Org. Biomol. Chem., 2006)

(untitled) - Leet, J. E.; Schroeder, D. R.; Langley, D. R.; Colson, K. L.; Huang, S.; Klohr, S. E.; Lee, M. S.; Golik, J.; Hofstead, S. J.; Doyle, T. W.; Matson, J. A. (J. Am. Chem. Soc., 1993)

(untitled) - Hashimoto, M.; Murakami, T.; Funahashi, K.; Tokunaga, T.; Nihei, K.-i.; Okuno, T.; Kimura, T.; Naoki, H.; Himeno, H. (Bioorg. Med. Chem., 2006)

(untitled) - Corte, J. R.; Fang, T.; Hangeland, J. J.; Friends, T. J.; Rendina, A. R.; Luettgen, J. M.; Bozarth, J. M.; Barbera, F. A.; Rossi, K. A.; Wei, A.; Ramamurthy, V.; Morin, P. E.; et al. (Bioorg. Med. Chem. Lett., 2015)

(untitled) - Mori, Y.; Ogawa, Y.; Mochikuzi, A.; Nakamura, Y.; Fujimoto, T.; Sugita, C.; Miyazaki, S.; Tamaki, K.; Nagayama, T.; Nagai, Y.; Inoue, S.-i.; Chiba, K.; et al. (Bioorg. Med. Chem., 2013)

(untitled) - Liu, Y.; Lang, Y.; Patel, N. K.; Ng, G.; Laufer, R.; Li, S.-W.; Edwards, L.; Forrest, B.; Sampson, P. B.; Feher, M.; Ban, F.; Awrey, D. E.; et al. (J. Med. Chem., 2015)

(untitled) - Ren, F.; Hogan, P. C.; Anderson, A. J.; Myers, A. G. (J. Am. Chem. Soc., 2007)

(untitled) - Shin, C.-g.; Okabe, A.; Ito, A.; Ito, A.; Yonezawa, Y. (Bull. Chem. Soc. Jpn., 2002)

(untitled) - Zou, Y.; Liu, Q.; Deiters, A. (Org. Lett., 2011)

(untitled) - Bagley, M. C.; Xiong, X. (Org. Lett., 2004)

(untitled) - Jones, M. C.; Marsden, S. P.; Muñoz-Subtil, D. M. (Org. Lett., 2006)

(untitled) - Jones, M. C.; Marsden, S. P. (Org. Lett., 2008)

(untitled) - Marsden, S. P.; Watson, E. L.; Raw, S. A. (Org. Lett., 2008)

(untitled) - Ja, Y.-X.; Hillgren, J. M.; Watson, E. L.; Marsden, S. P.; Kündig, E. P. (Chem. Commun., 2008)

(untitled) - Watson, E. L.; Marsden, S. P.; Raw, S. A. (Tetrahedron Lett., 2009)

(untitled) - Yousif, M. M.; Saeki, S.; Hamana, M. (Chem. Pharm. Bull., 1982)

(untitled) - Jones, G.; Pitman, M. A.; Lunt, E.; Lythgoe, D. J.; Abarca, B.; Ballesteros, R.; Elmasnaouy, M. (Tetrahedron, 1997)

(untitled) - Londregan, A. T.; Jennings, S.; Wei, L. (Org. Lett., 2011)

(untitled) - Londregan, A. T.; Burford, K.; Conn, E. L.; Hesp, K. D. (Org. Lett., 2014)

(untitled) - Lecointre, B.; Azzouz, R.; Bischoff, L. (Tetrahedron Lett., 2014)

(untitled) - Edgar, M. T.; Pettit, G. R.; Krupa, T. S. (J. Org. Chem., 1979)

(untitled) - Herdeis, C.; Gebhard, R. (Arch. Pharm., 1987)

(untitled) - Seebach, D. (Angew. Chem., Int. Ed. Engl., 1979)

(untitled) - Matsumoto, M.; Harada, M.; Yamashita, Y.; Kobayashi, S. (Chem. Commun., 2014)

(untitled) - Liu, X.; Gao, A.; Ding, L.; Xu, J.; Zhao, B. (Org. Lett., 2014)

(untitled) - Wu, Y.; Hu, L.; Li, Z.; Deng, L. (Nature, 2015)